Prospective randomized controlled trial investigating the type of sutures used during hepatectomy - Harimoto, Norifumi (Baishideng Publishing Group Co., Limited, 2011)
AIM: To determine whether absorbable sutures or non-absorbable sutures are better in preventing surgical site infection (SSI), in this paper we discuss the results of a randomized clinical trial which examined the type of sutures used during hepatectomy. METHODS: All hepatic resections performed from January 2007 to November 2008 at the Department of Surgery at Iizuka Hospital in Japan were included in this study. There were 125 patients randomly assigned to an absorbable sutures (Vicryl) group or non-absorbable sutures (Silk) group. RESULTS: SSI was observed in 13.6% (17/125) patients participating in this study, 11.3% in the Vicryl group and 15.8% in the Silk group. Incisional SSI including superficial and deep SSI, was observed in 8% of the Vicryl group and 9.5% of the Silk group. Organ/space SSI was observed in 3.2% of the Vicryl group and 6.0% of the Silk group. There were no significant differences, but among the patients with SSI, the period for recovery was significantly shorter for the Vicryl group compared to the Silk group. CONCLUSION: The incidence of SSI in patients receiving absorbable sutures and silk sutures is not significantly different in this randomized controlled study; however, the period for recovery in patients with SSI was significantly shorter for absorbable sutures.